Energy Consumption, Economic Growth and CO2 Emissions: Evidence from Panel Data for MENA Region - Farhani, Sahbi; Ben Rejeb, Jaleleddine (International Journal of Energy Economics and Policy, 2012)
Energy plays a vital role in economic development. It performs a key for sustainable development. Hence, many studies have attempted to look for the direction of causality between energy consumption (EC), economic growth (GDP) and CO2 emissions. This paper, therefore, applies the panel unit root tests, panel cointegration methods and panel causality test to investigate the relationship between EC, GDP and CO2 emissions for 15 MENA countries covering the annual period 1973-2008. The finding of this study reveals that there is no causal link between GDP and EC; and between CO2 emissions and EC in the short run. However, in the long run, there is a unidirectional causality running from GDP and CO2 emissions to EC. In addition, to deal with the heterogeneity in countries and the endogeneity bias in regressors, this paper applies respectively the FMOLS and the DOLS approach to estimate the long-run relationship between these three factors. Keywords: MENA countries; Energy consumption; Economic growth; CO2 emissions; Panel cointegration; Panel causality JEL Classifications: C33; O13; Q43